Searching and parasitism of diatraea saccharalis (lepidoptera: crambidae) by trichospilus diatraeae (hymenoptera: eulophidae) (2013)
The ability of Trichospilus diatraeae Cherian and Margabandhu, 1942 (Hymenoptera: Eulophidae) to search and parasitize Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) pupae in sugarcane stalks was evaluated. To analyze the ability for search and parasitism were used stalks of sugarcane (20 cm) where it was introduced a pupa of D. saccharalis (T1); a pupa and a caterpillar (T2) or a pupa and fecal matter (T3). Each stalk was placed in a transparent plastic bottle with 21 females of T. diatraeae. These pupae were isolated, after 72 h, in glass tubes at 25 ± 2 ºC, 70 ± 10 % relative humidity, 14:10 light/dark. The experiment was developed in an entirely casualized design with three treatments and 12 repetitions. Percentage of D. saccharalis pupa parasitized by T. diatraeae was 50.00 %, 83.33 % and 16.66 % in the T1, T2 and T3, respectively (c2 = 3.896, p=0.04). The presence of D. saccharalis caterpillars favored searching and parasitism of this host.La capacidad de Trichospilus diatraeae Cherian y Margabandhu, 1942 (Hymenoptera: Eulophidae) para buscar y parasitar las pupas de Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) en los tallos de la caña de azúcar fue estudiada. Para analizar la habilidad de búsqueda y parasitismo fueron utilizados tallos de la caña de azúcar (20 cm) donde se introdujo una pupa de D. saccharalis (T1); pupas y orugas (T2) o pupa y residuos fecales (T3). Cada tallo fue colocado en una botella plástica transparente con 21 hembras de T. diatraeae. Esas pupas fueron individualizadas, luego de 72 h, en tubos de vidrio a 25 ± 1°C, 70 ± 10 % UR y 14 h de foto período. El experimento se desarrolló en un diseño completamente al azar, con tres tratamientos y 12 repeticiones. Los porcentajes de pupas de D. saccharalis parasitados por T. diatraeae fueron del 50,00 %, 83,33 % y 16,66 % en el T1, T2 y T3, respectivamente (c2 = 3.896, p = 0,04). La presencia de D. saccharalis en los tallos de caña de azúcar favorecieron la búsqueda y parasitismo de su hospedero.